Computational bases study for complexes containing Cd (II) and biological evaluation in silico (Research, Society and Development, 2021)
Computational chemistry only gained international recognition after making a significant contribution to the scientific advances that resulted in Nobel prizes. With the technological evolution of the last decades, software was created with the aim of studying, investigating and understanding chemical processes at the molecular level of experimental studies. This promoted research agility and reduced costs with laboratory work. In this work, 5 different sets of computational bases were studied: STO-3G, LAN2DZ, SDD, 3-21G and DGDZVP, using the GaussView 5 and Gaussian 09w software with the DFT and B3LYP functional hybrid method. The distance and angle parameters of the di-u-chloro-bis complex [chlorine (4,7-dimethyl-1,10-phenanthroline) cadmium (II)] were obtained. The RMSD values obtained for each of the bases were observed. Molecular docking test was performed for each base, to verify which one had better parameters. It was noted in this study that the set of SDD bases presented the best results in the tests, being classified as the most suitable for studies of structures containing the element cadmium in its composition.